Electronic 1/f noise as a probe of dimensional effects on spin-glass dynamics - Harrison, David C. (Frontiers in Physics, 2024)
Over the past decade, spin-glass simulations have improved to the point that they now access time-and length-scales comparable to experiments at the mesoscale. A recent series of thin-film field-cooled/zero-field-cooled magnetization (FC/ZFC) experiments demonstrated activated spin dynamics, with a (temperature-independent) activation energy proportional to the logarithm of the film thickness, and with coefficients in remarkable agreement with simulation. These measurements require the application of a small magnetic fields, which has been shown to affect the spin-glass energy landscape. Measurements of the 1/f noise in metallic spin-glasses have been previously shown to be a sensitive probe of the spin-dynamics, and the measurements can be made without applying a magnetic field. Here, we review these techniques, and discuss how transport measurements can fit into the current landscape of spin-glass measurements. We compare previous measurements to more recent measurements on similar films, made with ostensibly different cooling protocols, and compare both the previous and recent measurements to the magnetometry. The transport measurements-taken over a wider range of temperature than the magnetometry-suggest that the maximum spin-glass energy barrier height is temperature-dependent, not fixed, possibly due to twodimensional dynamics. We discuss this possibility, along with future measurements which may be able to resolve this mystery.